The Effect Of Social Media On Students' Learning Achievement At SMA Negeri 6 Binjai (Pena Cendekia Insani, 2022)
This study aims to determine the effect of social media on student achievement at SMA Negeri 6 Binjai. The research method used is quantitative method. The sampling technique and population used were students of SMA Negeri 6 Binjai class XII Social Studies Department totaling 33 students from the class of 2021. By using the purposive sampling method, a sample of 33 students was determined from 811 populations. The data usage technique that the author uses is the questionnaire method (questionnaire). And the data analysis techniques used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test and simple linear regression test. The researcher used the Statistical Program for Social Science (SPSS) computer program version 21.0 to process the data. Based on the results of the study, it was obtained that t arithmetic > t table or 4,585 > 2.0395 with a significance value of 0.00 < 0.05. From the results of the t test, it was found that Ha was accepted. It can be concluded that there is a significant relationship between social media on student achievement at SMA Negeri 6 Binjai.